The Relationship between Ergonomic Posture and the Prevalence of Musculoskeletal Disorders among Workshop Employees in the West of Isfahan Province - Sara Karimi Zeverdegani; Amir Hossein Molla Agha Babaei; Fatemeh Paridokht (تحقیقات سلامت در جامعه, 2023)
Introduction and purpose: Following respiratory problems, musculoskeletal disorders are the second leading health concern in the world. The present study aimed to explore ergonomic posture and the prevalence of musculoskeletal disorders in workshop employees in the west of Isfahan province. Methods: This descriptive analytical study was conducted on 74025 people working in 9 different industrial group in the workshops of the West of Isfahan province in 2019. The samples were selected by census sampling method. In order to investigate the ergonomic condition and muscular-skeletal disorders of the workers, after taking photos of different tasks, RULA, REBA and QEC, WISHA, and OWAS methods were used to evaluate the posture of the workers. Finally, the collected data were analyzed in SPSS software (version 26) using descriptive statistics and Spearman's rank correlation coefficient. Results: This study indicated the high prevalence of musculoskeletal disorders in back pain (2,806 people). Moreover, there was a statically significant relationship between people with back pain and those who push and lower the load (P<0.05). Furthermore,  improper posture and repetitive work were the most frequent risk factors. Conclusion: Determining the incidence of musculoskeletal disorders and evaluating the ergonomic status of employees using posture assessment tools in western industries of Isfahan province revealed that ergonomic problems are high in employees' working environment. To reduce the prevalence of musculoskeletal disorders and minimize their effects in the studied community, it is necessary to reduce the risk level of ergonomic factors from risk level 4 to risk level 1. Therefore, ergonomic training and intervention programs should be considered for the employees of these industries to prevent possible and serious injuries in the future.